Peptides as cancer vaccines. (August 2019) - Calvo Tardón, Marta; Allard, Mathilde; Dutoit, Valérie; Dietrich, Pierre-Yves; Walker, Paul R
Highlights: Peptide cancer vaccines are safe, but have low therapeutic effect. New epitopes are being discovered through genomics, peptidomics, and bioinformatics. High throughput technologies make personalized peptide vaccines feasible. Peptide vaccine efficacy depend on strong adjuvants and immunomodulators. Optimal combination therapies for clinical application are still to be identified. Abstract : Cancer vaccines based on synthetic peptides are a safe, well-tolerated immunotherapy able to specifically stimulate tumor-reactive T cells. However, their clinical efficacy does not approach that achieved with other immunotherapies such as immune checkpoint blockade. Nevertheless, major advances have been made in selecting tumor antigens to target, identifying epitopes binding to classical and non-classical HLA molecules, and incorporating these into optimal sized peptides for formulation into a vaccine. Limited potency of currently used adjuvants and the immunosuppressive tumor microenvironment are now understood to be major impediments to vaccine efficacy that need to be overcome. Rationally designed combination therapies are now being tested and should ultimately enable peptide vaccination to be added to immuno-oncology treatment options.